Electro-galvanizing method with corrosion and chemical resistance of sus 304 grade
Patent Information
- Application Number
- CN202610429917.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-02
- Filing Date
- 2026-04-02
- Publication Date
- 2026-10-16
AI Technical Summary
然而,在铬酸盐处理过程中,存在产生如六价铬(Cr6+)和三价铬(Cr3+)等环境有害物质的问题
[0016] According to the electroplating method of the present invention, the use of sulfuric acid, hydrochloric acid, nitric acid, etc., is eliminated in the pretreatment process for electroplating steel, thus preventing hydrogen embrittlement of the steel. Therefore, the steel retains its tensile strength, impact resistance, and durability even after electroplating, and the adhesion between the steel and the electroplated layer is excellent. Furthermore, since the use of sulfuric acid, hydrochloric acid, nitric acid, etc., is eliminated in the electroplating process, wastewater generated from the use of these components can be prevented or minimized. Moreover, through a multi-layer surface treatment structure, corrosion resistance exceeding 1000 hours in a salt spray test (SST) and chemical resistance remaining undamaged after immersion in 10% hydrochloric acid for 3 minutes can be achieved, thus achieving performance similar to SUS304 stainless steel, which is unattainable with existing electroplating methods. This provides similar performance at 30-40% of the cost of SUS304, and therefore can replace SUS304 in applications such as steel pipes, pipe fittings, and flanges where SUS304 was originally used.
Smart Images

Figure CN122918657A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for electroplating zinc on steel, and more particularly to an electroplating zinc method having corrosion resistance and chemical resistance comparable to SUS304 stainless steel. Background Technology
[0002] Electro-zinc plating utilizes the sacrificial anode effect of zinc and iron, where zinc corrodes while iron is protected from corrosion, thus preventing steel corrosion. Typically, electro-zinc plating involves a series of processes, including: immersing the steel to be plated in a solution composed of alkaline components and surfactants for a certain period to degrease and clean it; rinsing the steel multiple times with water; immersing the steel to be plated in a solution composed of sulfuric acid and hydrochloric acid for a certain period to degrease and clean it; rinsing the steel multiple times with water; electro-zinc plating the cleaned steel; immersing the zinc-plated steel in a solution composed of nitric acid for a certain period to activate it; and chromate treatment of the zinc-plated steel.
[0003] However, according to existing processes, sulfuric acid and hydrochloric acid must be used in the pretreatment process before electroplating steel to remove rust, foreign matter, and oil. These acids exacerbate the hydrogen embrittlement of steel. Therefore, when steel pretreated with sulfuric acid and hydrochloric acid is electroplated, its tensile strength, durability, and impact resistance may actually decrease.
[0004] Furthermore, the sulfuric acid, hydrochloric acid, and nitric acid used in the pretreatment process are harmful to human health and the environment, necessitating wastewater treatment, which increases process complexity and cost. Moreover, after electroplating zinc onto steel, chromate treatment is required to improve corrosion resistance and achieve surface gloss. However, chromate treatment generates environmentally harmful substances such as hexavalent chromium (Cr6+) and trivalent chromium (Cr3+).
[0005] To address these issues, Korean Patent No. 10-2126747 discloses a method for electroplating zinc onto steel. This method uses a process solution containing linear alkylbenzene sulfonic acid, a complex organic-inorganic acid, ammonium chloride, sodium chloride, C9-11 ethoxylated alcohols, and a balance of water for pretreatment. After electroplating, a chromium-free surface treatment composition containing ethyl silicate, hydrochloric acid, ethanol, isopropanol, methoxysilane compounds, and deionized water is used for surface coating. This improves adhesion, brittleness resistance, and corrosion resistance. However, this method still cannot achieve the corrosion and chemical resistance sufficient to replace stainless steel such as SUS304 used in saltwater or acidic environments. Therefore, the high cost of using stainless steel remains a current necessity.
[0006] Therefore, it is necessary to develop an electroplating zinc process to solve the above problems. This process eliminates the use of sulfuric acid, hydrochloric acid, nitric acid, etc. in the pretreatment process before electroplating zinc, thereby not only preventing hydrogen embrittlement of steel, but also minimizing the generation of wastewater. It can achieve SUS304 level corrosion resistance and chemical resistance without the need for chromate treatment as a post-treatment for electroplating zinc. Moreover, the overall process is simple and time-saving. Summary of the Invention
[0007] Technical issues
[0008] The purpose of this invention is to provide an electroplating zinc method that is lower in cost than SUS304 and has corrosion resistance and chemical resistance comparable to SUS304, in order to solve the above-mentioned problems. In the pretreatment process of electroplating zinc on steel, this electroplating zinc method eliminates the use of sulfuric acid, hydrochloric acid, nitric acid, etc., thereby not only preventing hydrogen embrittlement of steel and minimizing wastewater generation, but also achieving SUS304-level corrosion resistance (more than 1000 hours of salt spray test) and chemical resistance (no damage after immersion in 10% hydrochloric acid for 3 minutes) without the need for chromate treatment in the post-treatment process after electroplating zinc.
[0009] Technical solution
[0010] To address the aforementioned problems, this invention provides an electroplating zinc method with SUS304-level corrosion and chemical resistance, comprising: a hot water cleaning step, immersing the steel to be plated in water at 60-80°C; a cleaning step, immersing the steel in a process solution and then subjecting it to ultrasonic treatment; a neutralization step, washing the steel at least once and then immersing it in an alkaline solution for neutralization; a plating step, electroplating the neutralized steel with zinc; an activation step, immersing the electroplated steel in the process solution for activation; a first surface coating step, coating the activated steel with a first chromium-free surface treatment composition; a second surface coating step, coating the coated steel with a second nano-ceramic surface treatment composition; and a heat treatment step, heat-treating the coated steel. The process solution comprises linear alkylbenzene sulfonic acid, a complex organic-inorganic acid, ammonium chloride, and sodium chloride. The first chromium-free surface treatment composition comprises ethyl silicate, hydrochloric acid, ethanol, isopropanol, methoxysilane compounds, and deionized water. The second nano-ceramic surface treatment composition comprises nano-silica particles, titanium alkoxide, zirconium alkoxide, glycidyl etheroxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, ethanol, deionized water, and acetic acid.
[0011] In one embodiment of the present invention, the chromium-free surface treatment composition may contain 45-60% by weight of ethyl silicate, 0.1-4% by weight of hydrochloric acid, 10-25% by weight of ethanol, 2-7% by weight of isopropanol, 5-15% by weight of methoxysilane compounds, and 10-20% by weight of deionized water, based on the total weight of the chromium-free surface treatment composition.
[0012] In another embodiment of the present invention, the second nano-ceramic surface treatment composition may contain, by weight, 1-5% nano-silica particles (20-50 nm), 3-7% titanium alkoxide, 3-7% zirconium alkoxide, 5-10% glycidyl etheroxypropyltrimethoxysilane, 3-7% 3-aminopropyltriethoxysilane, 50-70% ethanol, and 5-15% deionized water.
[0013] In another embodiment of the present invention, the heat treatment step may be performed at a temperature of 200-220°C for 30-40 minutes.
[0014] In another embodiment of the present invention, the nano-silica particles can be ultrafine particles with a particle size of 20-50 nm.
[0015] The effects of the invention
[0016] According to the electroplating method of the present invention, the use of sulfuric acid, hydrochloric acid, nitric acid, etc., is eliminated in the pretreatment process for electroplating steel, thus preventing hydrogen embrittlement of the steel. Therefore, the steel retains its tensile strength, impact resistance, and durability even after electroplating, and the adhesion between the steel and the electroplated layer is excellent. Furthermore, since the use of sulfuric acid, hydrochloric acid, nitric acid, etc., is eliminated in the electroplating process, wastewater generated from the use of these components can be prevented or minimized. Moreover, through a multi-layer surface treatment structure, corrosion resistance exceeding 1000 hours in a salt spray test (SST) and chemical resistance remaining undamaged after immersion in 10% hydrochloric acid for 3 minutes can be achieved, thus achieving performance similar to SUS304 stainless steel, which is unattainable with existing electroplating methods. This provides similar performance at 30-40% of the cost of SUS304, and therefore can replace SUS304 in applications such as steel pipes, pipe fittings, and flanges where SUS304 was originally used. Attached Figure Description
[0017] Figure 1 The photographs show the state of Example 3 and Comparative Example 6 before and after 1200 hours of continuous salt spray testing.
[0018] Figure 2 The photographs show the state of Example 3 and Comparative Example 6 before and after immersion in hydrochloric acid for 3 minutes. Detailed Implementation
[0019] Hereinafter, various embodiments of the present invention are described with reference to the accompanying drawings. It should be understood that the present invention is not limited to the specific embodiments, but includes various modifications, equivalents, and / or alternatives to the embodiments of the present invention. In the description of the drawings, similar structural elements may use similar reference numerals.
[0020] In this document, expressions such as “have,” “may have,” “contain,” or “may contain” refer to the existence of the corresponding feature (e.g., structural elements such as numerical values, functions, operations, or components) and do not exclude the existence of additional features.
[0021] In this document, expressions such as “A or B”, “at least one of A and / or B” or “one or more of A and / or B” may include all possible combinations of the items listed together. For example, “A or B”, “at least one of A and B” or “at least one of A or B” may refer to: (1) including at least one A, (2) including at least one B, or (3) including at least one A and at least one B.
[0022] The expression “configured to” as used herein may be used interchangeably with, for example, “suitable for”, “having the capacity to”, “designed to”, “adapted to”, “made to”, or “capable of”, depending on the context. The term “configured to” does not necessarily mean “specifically designed to”.
[0023] The terminology used herein is for the purpose of describing particular embodiments only and may not be intended to limit the scope of other embodiments. Singular expressions may include plural expressions unless the context clearly indicates otherwise. The terms used herein, including technical or scientific terms, may have the same meaning as commonly understood by those skilled in the art. Terms used herein that are defined in a general dictionary may be interpreted as having the same or similar meaning as they have in the relevant technical context, and should not be interpreted as having an idealized or overly formal meaning unless explicitly defined herein. In some cases, even terms defined herein should not be construed as excluding the embodiments described herein.
[0024] The embodiments disclosed herein are provided for illustration and understanding of the disclosed technical content and are not intended to limit the scope of the invention. Therefore, the scope of this document should be interpreted to include all modifications or various other embodiments based on the technical concept of the invention.
[0025] The preferred embodiments of the present invention will now be described in detail. Prior to this, the terms and words used in this specification and claims should not be construed as limited to their ordinary or dictionary meanings, but rather should be interpreted as meanings and concepts consistent with the technical concept of the present invention, based on the principle that the inventors may appropriately define terms and concepts for the purpose of best illustrating their invention.
[0026] Therefore, it should be understood that the structures of the embodiments described in this specification are only the most preferred embodiments of the present invention and do not represent all the technical ideas of the present invention. Therefore, various equivalent solutions and modifications that can replace them may exist when this application is submitted.
[0027] Throughout the specification, when a part is referred to as "including" a structural element, unless there is an explicit statement to the contrary, it does not exclude other structural elements, but rather implies that other structural elements may also be included.
[0028] The present invention will now be described in detail.
[0029] This invention relates to a method for electroplating zinc with SUS304 grade corrosion and chemical resistance, comprising: a hot water cleaning step, immersing the steel to be plated in water at 60-80°C; a cleaning step, immersing the steel in a process solution and then subjecting it to ultrasonic treatment; a neutralization step, washing the steel at least once and then immersing it in an alkaline solution for neutralization; a plating step, electroplating the neutralized steel with zinc; an activation step, immersing the electroplated steel in the process solution for activation; a first surface coating step, coating the activated steel with a first chromium-free surface treatment composition; a second surface coating step, coating the coated steel with a second nano-ceramic surface treatment composition; and a heat treatment step, heat-treating the coated steel. The process solution comprises linear alkylbenzene sulfonic acid, a complex organic-inorganic acid, ammonium chloride, and sodium chloride. The first chromium-free surface treatment composition comprises ethyl silicate, hydrochloric acid, ethanol, isopropanol, methoxysilane compounds, and deionized water. The second nano-ceramic surface treatment composition comprises nano-silica particles, titanium alkoxide, zirconium alkoxide, glycidyl etheroxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, ethanol, deionized water, and acetic acid.
[0030] In the hot water cleaning step, the steel to be plated is immersed in high-temperature water at 60-80°C. Specifically, the hot water cleaning step of the present invention can be performed by repeatedly immersing the steel to be plated in high-temperature water at 60-80°C and then removing it. In the hot water cleaning step, foreign matter and oil stains on the surface of the steel to be plated can be removed, thereby cleaning and degreasing the steel. Furthermore, in the present invention, by performing the hot water cleaning step to preliminarily remove foreign matter and oil stains from the surface of the steel before performing the following cleaning steps, the service life of the process composition used in the cleaning steps can be extended.
[0031] In the hot water cleaning step, the temperature of the water can be 60-80℃, specifically 65-75℃, more specifically 70℃, but is not limited thereto.
[0032] In the hot water cleaning step, the steel to be plated is immersed in high-temperature water at 60-80°C. Specifically, the hot water cleaning step of the present invention can be performed by repeatedly immersing the steel to be plated in high-temperature water at 60-80°C and then removing it. In the hot water cleaning step, foreign matter and oil stains on the surface of the steel to be plated can be removed, thereby cleaning and degreasing the steel. Furthermore, in the present invention, by performing the hot water cleaning step to preliminarily remove foreign matter and oil stains from the surface of the steel before performing the following cleaning steps, the service life of the process composition used in the cleaning steps can be extended.
[0033] In the hot water cleaning step, the temperature of the water can be 60-80℃, specifically 65-75℃, more specifically 70℃, but is not limited thereto.
[0034] In the cleaning step, the steel to be plated is immersed in the process combination solution and then subjected to ultrasonic treatment. Specifically, in the cleaning step of the present invention, the steel to be plated is immersed in the process combination solution to ensure complete immersion, and then subjected to ultrasonic treatment to clean the steel to be plated. The process combination solution is a diluted solution prepared by diluting the process composition in water.
[0035] The cleaning steps described above can remove rust, dust, foreign matter, oil, and other contaminants from the surface of the steel to be plated. Rust removal, as described above, refers to rust removal, and oil removal, as described above, refers to degreasing.
[0036] The process composition comprises linear alkylbenzene sulfonic acid, a complex organic-inorganic acid, ammonium chloride, sodium chloride, C9-11 ethoxylated alcohols, and water. Specifically, based on the total weight of the process composition of the present invention, the process composition may comprise 4-5% by weight of linear alkylbenzene sulfonic acid, 30-33% by weight of the complex organic-inorganic acid, 11-13% by weight of ammonium chloride, 4-6% by weight of sodium chloride, 3-4% by weight of C9-11 ethoxylated alcohols, and the balance being water.
[0037] Linear alkylbenzene sulfonic acid can improve the cleaning performance of process compositions.
[0038] Composite organic-inorganic acids can enhance the cleaning performance of process compositions in removing rust, foreign matter, and oil stains. For example, composite organic-inorganic acids may include: organic acids selected from two or more of the group consisting of formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, acrylic acid, crotonic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, cinnamic acid, glycolic acid, citric acid, and levulinicacid; and inorganic acids selected from one or more of the group consisting of phosphoric acid and phosphorous acid, but are not limited thereto.
[0039] Specifically, the composite organic-inorganic acid may include citric acid, levulinic acid, and phosphoric acid. More specifically, the composite organic-inorganic acid may contain citric acid, levulinic acid, and phosphoric acid in a weight ratio of 1:0.3:5. In particular, when the composite organic-inorganic acid of the present invention contains citric acid, levulinic acid, and phosphoric acid in a weight ratio of 1:0.3:5, the rust removal, cleaning, and degreasing effects on steel are further improved, thereby preventing hydrogen embrittlement of the steel and achieving excellent adhesion between the steel and the electroplated zinc layer in the electroplating process.
[0040] Ammonium chloride is an ammonium salt that, in its pure state, is a transparent white water-soluble crystal. The ammonium chloride can enhance the cleaning effect of the process composition in removing rust, foreign matter, oil stains, etc.
[0041] Sodium chloride is a compound of sodium and chlorine, which can improve the cleaning effect of the process composition of the present invention in removing rust, foreign matter, oil stains, etc.
[0042] C9-11 alcohol ethoxylated is the main surfactant component, which can improve the cleaning effect of the process composition of the present invention. Specifically, C9-11 alcohol ethoxylated can remove foreign matter and oil stains.
[0043] The ultrasonic treatment can be performed by immersing the steel to be plated in a process solution until it is completely submerged, and then subjecting the process solution to ultrasonic treatment. Through this ultrasonic treatment, the steel to be plated can be cleaned and degreased simultaneously.
[0044] The ultrasonic treatment can be performed at a frequency of 30kHz to 35kHz, specifically within the range of 32kHz.
[0045] Furthermore, the ultrasonic treatment can vary depending on the size and shape of the steel, the amount of the process composition, etc., and is not particularly limited. For example, the ultrasonic treatment may involve immersing the steel in the process composition solution for 60 to 70 seconds, specifically 65 seconds.
[0046] When the ultrasonic treatment is performed in the cleaning step, the temperature of the process solution can be 50-52°C, specifically 51°C.
[0047] In the neutralization step, after the steel treated in the cleaning step is washed with water at least once, the steel is then immersed in an alkaline solution for neutralization. Specifically, in the neutralization step, the steel treated in the cleaning step can be washed with water 1 to 2 times, and then the washed steel can be immersed in an alkaline solution to ensure complete immersion and neutralization.
[0048] The alkaline solution can be a solution containing raw materials with hydroxyl groups, such as ammonium hydroxide, sodium hydroxide, calcium hydroxide, etc., or a solution containing raw materials capable of generating hydroxyl groups, such as quicklime or magnesium oxide, etc., but is not limited thereto. Specifically, the alkaline solution can be a solution containing 7% sodium hydroxide and water.
[0049] In the plating step, the steel neutralized in the neutralization step can be electroplated with zinc according to known methods. Specifically, in the plating step, an alkaline plating solution containing 15 g / L zinc oxide, 150 g / L sodium hydroxide, 25 g / L smoothing agent, 5 mL / L brightener, and 0.5 mL / L nonionic surfactant can be used, at a temperature of 30°C and 3 A / dm². 2 Electroplating of zinc is performed under the current density conditions to form a coating with a thickness of 15 to 20 μm.
[0050] In the activation step, the electrogalvanized steel is immersed in the process solution for activation. Specifically, the activation step can be carried out by completely immersing the electrogalvanized steel in the process solution for 10 seconds, wherein the composition of the process solution is the same as that in the cleaning step.
[0051] Typically, solutions containing nitric acid are used to activate electroplated steel. However, according to the present invention, a process combination solution made from the aforementioned process composition that does not contain hydrochloric acid, nitric acid, sulfuric acid, etc., can be used instead of the nitric acid-containing solution for activation. In other words, since the use of nitric acid can be eliminated, wastewater generation can be reduced, thus making it environmentally friendly.
[0052] In the first surface coating step, corrosion resistance can be significantly improved by forming a coating on the activated steel using a first chromium-free surface treatment composition.
[0053] Specifically, in the first surface coating step, the electroplated zinc steel is immersed in a first chromium-free surface treatment composition comprising ethyl silicate, hydrochloric acid, ethanol, isopropanol, methoxysilane compounds and deionized water, and then dried and cured, thereby forming a first coating on the electroplated zinc layer of the steel formed in the activation step.
[0054] Based on the total weight of the first chromium-free surface treatment composition, the first chromium-free surface treatment composition may contain 45-60% by weight of ethyl silicate, 0.1-4% by weight of hydrochloric acid, 10-25% by weight of ethanol, 2-7% by weight of isopropanol, 5-15% by weight of methoxysilane compounds, and 10-20% by weight of deionized water. Specifically, based on the total weight of the first chromium-free surface treatment composition, the first chromium-free surface treatment composition may contain 55% by weight of ethyl silicate, 1.5% by weight of hydrochloric acid, 18% by weight of ethanol, 5% by weight of isopropanol, 10% by weight of methoxysilane compounds, and 10.5% by weight of deionized water.
[0055] Ethyl silicate imparts strong crystallinity to sand or refractory materials and precipitates silica from the solution during drying. The ethyl silicate can improve the adhesion between the electroplated zinc layer formed on steel and the coating formed by the first chromium-free surface treatment composition of the present invention, while also improving corrosion resistance, rust prevention, resistance to blackening, and resistance to white rust. Specifically, ethyl silicate can improve the density of the microstructure by hydrolyzing to form polysilicates. Furthermore, the adhesion between the electroplated zinc layer and the coating formed by the first chromium-free surface treatment composition of the present invention can be improved by forming zinc-silicon bonds at the interface between the electroplated zinc layer and the coating.
[0056] Hydrochloric acid can be used as a catalyst to promote the hydrolysis of ethyl silicate.
[0057] Ethanol can be used to adjust the flowability and viscosity of the first chromium-free surface treatment composition of the present invention. Furthermore, it can make the thickness of the electroplated zinc layer uniform and give it a flat surface.
[0058] Isopropanol can improve the stability of the first chromium-free surface treatment composition of the present invention and adjust its flowability and viscosity.
[0059] Methoxysilane compounds may contain glycidoxypropyltrimethoxysilane and methyltrimethoxysilane in a weight ratio of 1:1.5.
[0060] The glycidyl etheroxypropyltrimethoxysilane can improve the adhesion of the first chromium-free surface treatment composition of the present invention, and improve its flowability by preventing excessive increase in viscosity. The methyltrimethoxysilane can improve the water resistance of the coating film formed using the first chromium-free surface treatment composition of the present invention, and give it a self-cleaning effect.
[0061] Deionized water helps to hydrolyze ethyl silicate. In the presence of deionized water, ethyl silicate hydrolyzes to form polysilicate, thus achieving the effect described above.
[0062] In the second surface coating step, the steel coated with the first chromium-free surface treatment composition is then coated with a second nano-ceramic surface treatment composition. This process further improves chemical resistance and corrosion resistance.
[0063] Specifically, in the second surface coating step, the steel coated with the first chromium-free surface treatment composition is immersed in a second nano-ceramic surface treatment composition comprising nano-silica particles, titanium alkoxide, zirconium alkoxide, glycidyl etheroxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, ethanol and deionized water, and then dried and cured, thereby forming a second coating on top of the first coating.
[0064] Based on the total weight of the second nano-ceramic surface treatment composition, the second nano-ceramic surface treatment composition may contain 1-5 weight percent of nano-silica particles (20-50 nm), 3-7 weight percent of titanium alkoxide, 3-7 weight percent of zirconium alkoxide, 5-10 weight percent of glycidyl etheroxypropyltrimethoxysilane, 3-7 weight percent of 3-aminopropyltriethoxysilane, 50-70 weight percent of ethanol, and 5-15 weight percent of deionized water. Specifically, based on the total weight of the second nano-ceramic surface treatment composition, the second nano-ceramic surface treatment composition may contain 3 weight percent of nano-silica particles (20-50 nm), 5 weight percent of titanium alkoxide, 5 weight percent of zirconium alkoxide, 7 weight percent of glycidyl etheroxypropyltrimethoxysilane, 5 weight percent of 3-aminopropyltriethoxysilane, 65 weight percent of ethanol, and 10 weight percent of deionized water.
[0065] Nano-silica particles, with a particle size of 20–50 nm, are ultrafine particles that can improve the mechanical strength and hardness of the coating and impart wear resistance. Furthermore, the filling effect of the nanoparticles enhances the density of the coating, effectively blocking the penetration of external corrosive agents.
[0066] Titanium alkoxides and zirconium alkoxides form an inorganic network through hydrolysis and condensation reactions, thereby creating a ceramic-grade coating with excellent chemical resistance and wear resistance. In particular, titanium-based and zirconium-based compounds exhibit excellent resistance to acids and alkalis, providing superior chemical resistance even in strong acid environments such as 10% hydrochloric acid.
[0067] Glycidyl etheroxypropyltrimethoxysilane enhances the chemical stability of the coating by forming covalent bonds with other components through its epoxy groups. Furthermore, it contributes to the formation of an organic-inorganic hybrid network, thereby imparting flexibility and impact resistance to the coating.
[0068] 3-Aminopropyltriethoxysilane contains an amino group (-NH2), which provides strong adhesion to metal surfaces, especially improving corrosion resistance in acidic environments. The amino group undergoes protonation, acting as a buffer to maintain the stability of the coating even in acidic conditions.
[0069] Ethanol acts as a solvent for the other components and adjusts the viscosity and flowability of the coating solution. An appropriate amount of ethanol helps to form a uniform coating during application.
[0070] Deionized water is essential for the hydrolysis of metal alkoxides. It can promote the hydrolysis of silane compounds to form active silanol (Si-OH) groups, which are then used to build enhanced network structures through condensation reactions.
[0071] In the heat treatment step of this invention, the steel coated with the second nano-ceramic surface treatment composition is heat-treated. The heat treatment process further improves its corrosion resistance and chemical resistance by promoting coating curing and densification.
[0072] Specifically, the heat treatment step can be carried out at a temperature of 200-220°C using a hot air circulating oven for 30-40 minutes.
[0073] Through heat treatment, the following changes can be achieved: complete removal of residual solvents within the second nano-ceramic surface treatment composition coating; completion of the hydrolysis and condensation reactions of silane compounds; complete ceramicization of metal alkoxides (titanium, zirconium); enhanced interfacial bonding between nano-silica particles and the metal oxide and siloxane networks; and densification of the coating's internal structure while reducing porosity. These changes significantly improve the durability, chemical resistance, and corrosion resistance of the multilayer coating structure, enabling it to achieve SUS304-level performance.
[0074] Preparation Example 1: Preparation of process compositions and process liquid combinations
[0075] A process composition was prepared by mixing the components according to the composition shown in Table 1 below. Then, the process composition was mixed and diluted with 20 parts by weight of water relative to 100 parts by weight to prepare a process solution.
[0076] Table 1
[0077]
[0078] Preparation Example 2: Preparation of the First Chromium-Free Surface Treatment Composition
[0079] The first chromium-free surface treatment composition was prepared by mixing the components according to the composition shown in Table 2 below.
[0080] Table 2
[0081]
[0082] Examples and Comparative Examples
[0083] The following examples illustrate the excellent adhesion, brittleness resistance, corrosion resistance, and chemical resistance of the electroplating zinc method of the present invention. These examples are for illustrative purposes only and should not be construed as limiting the scope of the invention.
[0084] Prepare a steel flange and immerse it in hot water at 70°C. After removing the steel flange from the hot water, immerse it completely in the process solution prepared in Preparation Example 1, and then clean it by ultrasonic treatment at a frequency of approximately 32 kHz for approximately 65 seconds. At this time, the temperature of the process solution is approximately 51°C. The cleaning removes rust, foreign matter, oil, etc. from the surface. Afterward, wash the steel flange twice with water and immerse it completely in a 7% sodium hydroxide aqueous solution for approximately 15 seconds to neutralize it. Then, electroplat the neutralized steel flange with zinc. The electroplating uses an alkaline plating solution containing 15 g / L zinc oxide, 150 g / L sodium hydroxide, 25 g / L smoothing agent, 5 mL / L gloss agent, and 0.5 mL / L nonionic surfactant, at a temperature of 30°C and 3 A / dm². 2 The plating is carried out under current density conditions, with a coating thickness of 15–20 μm. At this point, while keeping the above component ratios unchanged, the alkaline plating solution ratio is scaled up to match the steel flange dimensions.
[0085] The electroplated zinc steel flange is immersed in the process solution prepared in Preparation Example 1 for about 10 seconds to completely submerge it and activate the electroplated zinc layer. Then it is washed with water 1 to 2 times. After that, it is immersed in the first chromium-free surface treatment composition prepared in Preparation Example 2 to completely submerge it. Then it is dried by coating desolvation (spin method, 300 to 400 rpm) for 10 to 20 seconds and dried at room temperature for 10 minutes to form a first coating on the electroplated zinc layer using the first chromium-free surface treatment composition.
[0086] Subsequently, the steel flange with the first coating formed thereon is immersed in the second nano-ceramic surface treatment composition having the composition shown in Table 3 below, so that it is completely submerged, and then dried by coating dehydration (spin method, 300-400 rpm) for 10-20 seconds, and then dried at room temperature for 10 minutes, so as to form a second coating on the first coating using the second nano-ceramic surface treatment composition.
[0087] The steel flange with the first coating and the second coating formed thereon is subjected to heat treatment for 35 minutes at a temperature of 210°C using a hot air circulating oven.
[0088] Comparative Example 6
[0089] Flanges made of SUS304 material were prepared.
[0090] Comparative Example 7
[0091] Flanges were prepared in which the first coating was formed using the same process as in Comparative Examples 1 to 5, but no second coating was formed.
[0092] Table 3
[0093]
[0094] Experimental Example
[0095] Experimental Example 1: Corrosion Resistance Assessment (Salt Spray Test Method KS D 9502 Test Standard)
[0096] Flanges from Examples 1 to 5 and Comparative Examples 1 to 7 were placed in a 5% brine solution and subjected to a continuous salt spray test for 720 hours. The test durations were extended to 1000 hours, 1200 hours, and 1500 hours, respectively. After each duration, the salt on the flange surface was removed with running water (below 35°C) and dried with compressed air at a temperature below 40°C. Subsequently, the presence of white rust or red rust was visually confirmed, and the corrosion-affected areas were examined in detail using an optical microscope (10–50x). The evaluation results are shown in Table 4 below.
[0097] Table 4
[0098]
[0099] (×: No rust produced (qualified), O: Rust produced (unqualified))
[0100] Referring to Table 4 above, it can be confirmed that Examples 1 to 5 did not corrode after 1000 hours of continuous corrosion, and Examples 3 and 5, like SUS304 (Comparative Example 6), did not corrode after 1200 hours of continuous corrosion, thus exhibiting excellent corrosion resistance. Figure 1 To show photographs of the states of Example 3 and Comparative Example 6 before and after 1200 hours of continuous salt spray testing, refer to... Figure 1 It can be confirmed that the surface condition of the flange of Example 3 is almost the same as that of the flange made of SUS304 material after 1200 hours.
[0101] Experimental Example 2: Chemical Resistance Assessment (Immersion in 10% Hydrochloric Acid for 3 minutes)
[0102] The initial weights of the flanges in Examples 1 to 5 and Comparative Examples 1 to 7 were measured using an analytical precision balance. They were then completely immersed in a 10% hydrochloric acid (HCl) solution (room temperature) for 3 minutes, followed by rinsing the surface with deionized water for 1 minute, removing surface moisture with compressed air, and drying at room temperature for 1 hour. Their weights were then measured again using an analytical precision balance, and the weight loss relative to the initial weight was measured. Furthermore, surface damage such as discoloration, reduced gloss, blistering, cracking, and peeling were visually assessed, and the results are shown in Table 5 below.
[0103] Table 5
[0104]
[0105] Referring to Table 5 above, it can be confirmed that the results observed in Examples 1 to 5 were no damage or only slight discoloration, and the weight reduction rate was only 0.07 to 0.18%, demonstrating excellent chemical resistance. Figure 2 To show photographs of the states of Example 3 and Comparative Example 6 before and after immersion in hydrochloric acid, refer to... Figure 2 It can be confirmed that after the flange of Example 3 was immersed in hydrochloric acid for 3 minutes, its surface condition was almost the same as that of the flange made of SUS304 material.
[0106] Experimental Example 3: Adhesion Assessment (ASTM D 3359)
[0107] Using a blade cutter, 25 square grid patterns of 1mm × 1mm were formed on the flange surfaces of Examples 1 to 5 and Comparative Examples 1 to 5. Then, translucent pressure-sensitive tape with an adhesive strength of 35–45 N / 100mm was applied, and pressure was applied with a pressure roller. After 90 seconds, the tape was pulled up and removed. The cut areas were inspected using a magnifying glass and a lighting device. The above process was repeated 10 times, and the average value was calculated and shown in Table 6 below.
[0108] Table 6
[0109]
[0110] 5B (0% peeling): The grid edges are completely smooth, with no square separation.
[0111] 4B (0% < peeling ≤ 5%): Small pieces of material separate at the intersection.
[0112] 3B (5% < peel ≤ 15%): Coating separation at grid edges and intersections.
[0113] 2B (15% < peeling ≤ 35%): The coating shows obvious separation along the grid edges.
[0114] 1B (35% < peel ≤ 65%): The coating is partially or completely separated on most of the grid.
[0115] 0B (stripping > 65%): The degree of stripping is more severe than all grades from 5B to 1B.
Claims
1. A method for electroplating zinc with SUS304-level corrosion resistance and chemical resistance, characterized in that, include: The hot water cleaning step involves immersing the steel to be plated in water at 60-80℃. The cleaning step involves immersing the steel in a process solution and then subjecting it to ultrasonic treatment. The neutralization step involves washing the steel with water at least once, and then immersing the steel in an alkaline solution for neutralization. The plating step involves electroplating zinc onto the neutralized steel. The activation step involves immersing the electro-galvanized steel in the process solution for activation. The first surface coating step involves coating the activated steel with a first chromium-free surface treatment composition; The second surface coating step involves coating the coated steel with a second nano-ceramic surface treatment composition; and The heat treatment step involves heat treating the coated steel. The process composition solution is a diluted solution prepared by diluting a process composition containing linear alkylbenzene sulfonic acid, a complex organic-inorganic acid, ammonium chloride, sodium chloride, C9-11 alcohol ethoxylate, and water in water. The first chromium-free surface treatment composition comprises ethyl silicate, hydrochloric acid, ethanol, isopropanol, methoxysilane compounds, and deionized water. The second nano-ceramic surface treatment composition comprises nano-silica particles, titanium alkoxide, zirconium alkoxide, glycidyl etheroxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, ethanol, deionized water, and acetic acid.
2. The electroplating zinc method with SUS304-level corrosion resistance and chemical resistance according to claim 1, characterized in that, Based on the total weight of the chromium-free surface treatment composition, the chromium-free surface treatment composition comprises 45-60% by weight of ethyl silicate, 0.1-4% by weight of hydrochloric acid, 10-25% by weight of ethanol, 2-7% by weight of isopropanol, 5-15% by weight of methoxysilane compounds, and 10-20% by weight of deionized water.
3. The electroplating zinc method with SUS304-level corrosion resistance and chemical resistance according to claim 1, characterized in that, Based on the total weight of the second nano-ceramic surface treatment composition, the second nano-ceramic surface treatment composition comprises 1-5 weight percent of nano-silica particles, 3-7 weight percent of titanium alkoxide, 3-7 weight percent of zirconium alkoxide, 5-10 weight percent of glycidyl etheroxypropyltrimethoxysilane, 3-7 weight percent of 3-aminopropyltriethoxysilane, 50-70 weight percent of ethanol, and 5-15 weight percent of deionized water, wherein the particle size of the nano-silica particles is 20-50 nm.
4. The electroplating zinc method with SUS304-level corrosion resistance and chemical resistance according to claim 1, characterized in that, The heat treatment step is carried out at a temperature of 200–220°C for 30–40 minutes.